Environmental and occupational risk factors for progressive supranuclear palsy: Case‐control study. Issue 5 (8th February 2016) - Litvan, Irene; Lees, Peter S.J.; Cunningham, Christopher R.; Rai, Shesh N.; Cambon, Alexander C.; Standaert, David G.; Marras, Connie; Juncos, Jorge; Riley, David; Reich, Stephen; Hall, Deborah; Kluger, Benzi; et al.
Abstract: Background: The cause of progressive supranuclear palsy (PSP) is largely unknown. Based on evidence for impaired mitochondrial activity in PSP, we hypothesized that the disease may be related to exposure to environmental toxins, some of which are mitochondrial inhibitors. Methods: This multicenter case‐control study included 284 incident PSP cases of 350 cases and 284 age‐, sex‐, and race‐matched controls primarily from the same geographical areas. All subjects were administered standardized interviews to obtain data on demographics, residential history, and lifetime occupational history. An industrial hygienist and a toxicologist unaware of case status assessed occupational histories to estimate past exposure to metals, pesticides, organic solvents, and other chemicals. Results: Cases and controls were similar on demographic factors. In unadjusted analyses, PSP was associated with lower education, lower income, more smoking pack‐years, more years of drinking well water, more years living on a farm, more years living 1 mile from an agricultural region, more transportation jobs, and more jobs with exposure to metals in general. However, in adjusted models, only more years of drinking well water was significantly associated with PSP. There was an inverse association with having a college degree. Conclusions: We did not find evidence for a specific causative chemical exposure; higher number of years of drinking well water is a risk factor for PSP. This result remained significant after adjusting for income, smoking, education and occupational exposures. This is the first case‐control study to demonstrate PSP is associated with environmental factors. © 2016 International Parkinson and Movement Disorder Society